Answer:
the statement shows the inverse property of addition as the sum of a number and its inverse is zero.
Step-by-step explanation:
As we know that Inverse Property of Addition states if you add any number to its opposite, the result will be zero.
For example, 13 + (-13) = 0 shows that -13 is the additive inverse of 13.
In other words, the sum of a number and its inverse is zero.
Now checking from the available options,
![0y+\left(-0y\right)](https://tex.z-dn.net/?f=0y%2B%5Cleft%28-0y%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28-a%5Cright%29%3D-a)
![=0\cdot \:y-0\cdot \:y](https://tex.z-dn.net/?f=%3D0%5Ccdot%20%5C%3Ay-0%5Ccdot%20%5C%3Ay)
![\mathrm{Add\:similar\:elements:}\:0\cdot \:y-0\cdot \:y=0](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3Asimilar%5C%3Aelements%3A%7D%5C%3A0%5Ccdot%20%5C%3Ay-0%5Ccdot%20%5C%3Ay%3D0)
![=0](https://tex.z-dn.net/?f=%3D0)
Thus,
![0\cdot \:y+\left(-0\cdot \:y\right)=0](https://tex.z-dn.net/?f=0%5Ccdot%20%5C%3Ay%2B%5Cleft%28-0%5Ccdot%20%5C%3Ay%5Cright%29%3D0)
Therefore,
the statement shows the inverse property of addition as the sum of a number and its inverse is zero.